2019
DOI: 10.1038/s41598-019-47789-y
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA profiling in Pinus pinaster reveals the transcriptome of developing seeds and highlights differences between zygotic and somatic embryos

Abstract: Regulation of seed development by small non-coding RNAs (sRNAs) is an important mechanism controlling a crucial phase of the life cycle of seed plants. In this work, sRNAs from seed tissues (zygotic embryos and megagametophytes) and from somatic embryos of Pinus pinaster were analysed to identify putative regulators of seed/embryo development in conifers. In total, sixteen sRNA libraries covering several developmental stages were sequenced. We show that embryos and megagametophytes expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 67 publications
(94 reference statements)
3
39
0
Order By: Relevance
“…Moreover, the auxin-related processes including auxin biosynthesis and signalling was placed in centre of SE and ZE regulation. However, recent RNAseq data of an embryogenic culture of Arabidopsis and Pinus pinaster showed that the SE-transcriptome seems to be distinctly different from the transcriptome of a zygotic embryo [170,171]. This unexpected finding suggests that the molecular events that trigger SE induction might differ from the ones that operate during ZE and points to the epigenetic processes that orchestrate the transcriptomes of in vitro cultured somatic cells in response to plethora of endo-and exogenous factors, thus making them different from those found in ZE.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Moreover, the auxin-related processes including auxin biosynthesis and signalling was placed in centre of SE and ZE regulation. However, recent RNAseq data of an embryogenic culture of Arabidopsis and Pinus pinaster showed that the SE-transcriptome seems to be distinctly different from the transcriptome of a zygotic embryo [170,171]. This unexpected finding suggests that the molecular events that trigger SE induction might differ from the ones that operate during ZE and points to the epigenetic processes that orchestrate the transcriptomes of in vitro cultured somatic cells in response to plethora of endo-and exogenous factors, thus making them different from those found in ZE.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Nevertheless, comparisons of function of miRNAs in somatic versus zygotic embryos in the future may reveal an miRNA-based regulation network of the embryonic differentiation events, with common or specific miRNAs to both processes. In the ongoing debate about the ZE and SE similarities, recent analyses of an embryogenic culture of Arabidopsis and Pinus pinaster showed that the SE transcriptome seems to be distinctly different from the transcriptome of a zygotic embryo [ 38 , 39 ]. That finding highlighted how important the precise identification of the function of miRNAs in each of the different phases of both analysed processes is, and the miRNA-dedicated tools for miRNA functional analysis can make it possible.…”
Section: Plant Mirnas What We Are Dealing With?mentioning
confidence: 99%
“…miRNA profiling using NGS has revolutionised miRNA analysis and there are still new instruments, sequencing platforms, and new methods that appear, such as sRNA-seq using single-cell sequencing [ 81 ] which provide new opportunities for analyses also during embryogenesis. Until now, sRNA-seq analyses have been performed during embryogenesis in Picea sprus [ 82 ], P. pinaster [ 39 ], Picea glauca [ 30 ], Triticum aestivum [ 83 ], Arabidopsis [ 28 , 30 , 35 , 38 , 41 , 84 ], Dimocarpus longan [ 85 ], Zea mays [ 86 ], Citrus sinensis [ 87 ], Larix leptolepis [ 88 ], Gossypium hirsutum [ 89 , 90 ], Phyllostachys heterocycla [ 91 ], Oryza sativa [ 92 ], and Lilium pumilum [ 93 ] (for SE reviewed in [ 94 ]). Plant embryogenesis is challenging to analyse due to the small, early embryos that are deeply embedded in the maternal tissues, which often results in RNA contamination from maternal tissue, and due to difficult distinguishing of the cells that are undergoing SE within an explant tissue, protocols, which are specifically dedicated for ZE and SE, have been developed and successfully used for miRNA analysis [ 28 , 38 , 84 , 95 ].…”
Section: Available Plant Mirna-dedicated Research Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the factors involved in the RdDM pathway, such as RNA-DEPENDENT RNA POLY-MERASE 2 (RDR2), DICER-LIKE 3 (DCL3), ARGONAUTE 4 (AGO4) and most of Pol IV and Pol V components, are conserved between angiosperms and gymnosperms [17,21]. Indeed, gymnosperms have identifiable 24-nt sRNA populations in male cones and embryonic tissues [18,[21][22][23][24][25], revealing tissue-specific differences in sRNA production and possibly function in gymnosperms. More than half of the genomes in most gymnosperm species are occupied by TEs [18,26].…”
Section: Introductionmentioning
confidence: 99%